Enhancing Writing Skills through Joyful Learning: A Comparative Study of Extroverted and Introverted Fourth-Semester English Department Students at a Public University in Banten - Prabowo, Jumbuh; Rahmawati, Eri; Aisah, Siti (Journal of Linguistics, Literacy, and Pedagogy, 2025)
The purpose of this study is to investigate how joyful learning strategies improve writing skills among extrovert and introverted students in the fourth semester of the English Department at one of the public universities in Banten province. The research question seeks to uncover variations in how extrovert and introvert students respond to joyful learning approaches in writing training. The study used a qualitative case study design, with eight subjects (four extroverts and four introverts) chosen by purposive sampling. The data collection methods included semi-structured interviews, observations of classes, and student reflective journals. Following the data collection, thematic analysis was applied. It was discovered that extrovert students prefer teaching methods that are more energetic, collaborative and allow for greater verbal expression, such as group writing games and peer dialogues. Introvert students, on the other hand, are far more engaged with individual reflective tasks like music-assisted writing and visual prompts. Nevertheless, both groups reported an increase in pleasure, a decrease in anxiety, and an enhancement of confidence with writing through the joyful learning methods employed. The study concludes that adapting the joyful learning strategies to fit personalities will enable writing instruction in EFL contexts to be more effective and more inclusive.